GAMBARAN WAKTU PENYEDIAAN DOKUMEN REKAM MEDIS RAWAT INAP DI RUMAH SAKIT SUMBER WARAS KABUPATEN CIREBON - Sri Dewi Wulan Sari; Loura Weryco Latupeirissa; Eka Martaviantika Gusana (LPPM ITEKES Mahardika, 2021)
Minimum service standards are a technical spesification regarding service benchmarks provided by public service bodies to the public. Minimum service standards have several fields especially in the field of medical records. One the indicators in the field of medical record is the time of provision of inpatient medical record documents. Minimum service standards based on Kepmenkes 129 of 2008 ≤ 15 minutes. The purpose of this study was to determine the time provision of inpatient medical record documents in Hospital Sumber Waras Cirebon Regency. The type of research used is descriptive research with a quantitative approach. The population in this study was 1.242 documents with a total sample of 92 documents and sampling in this study using accidental sampling. The research instrument used wa an observasion sheet in the form of a checklist sheet. Dat collection procedure is done by determining the inclusion and exclusion. Based on the results of research when providing inpatient medical record documents as much as 53% of 49 documents and 47% of 43 documents that are not appropriate. The average time for providing inpatient medical record documents is 23 minute 13 seconds. The conclusions obtained in this study are time for providing inpatient medical record documents in Hospital Sumber Waras Cirebon Regency source not in accordance with Kepmenkes standard number 129 of 2008, that for the time of providing inpatient medical record documents is ≤ 15 minutes.